PneumoniaCheck, a novel aerosol collection device, permits capture of airborne Mycobacterium tuberculosis and characterisation of the cough aeromicrobiome in people with tuberculosis - Tinaye L. Chiyaka; Georgina R. Nyawo; Charissa C. Naidoo; Suventha Moodley; Jose C. Clemente; Stephanus T. Malherbe; Robin M. Warren; David N. Ku; Leopoldo N. Segal; Grant Theron (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background Tuberculosis (TB), a major cause of disease and antimicrobial resistance, is spread via aerosols. Aerosols have diagnostic potential and airborne-microbes other than Mycobacterium tuberculosis complex (MTBC) may influence transmission. We evaluated whether PneumoniaCheck (PMC), a commercial aerosol collection device, captures MTBC and the aeromicrobiome of people with TB. Methods PMC was done in sputum culture-positive people (≥ 30 forced coughs each, n = 16) pre-treatment and PMC air reservoir (bag, corresponding to upper airways) and filter (lower airways) washes underwent Xpert MTB/RIF Ultra (Ultra) and 16S rRNA gene sequencing (sequencing also done on sputum). In a subset (n = 6), PMC microbiota (bag, filter) was compared to oral washes and bronchoalveolar lavage fluid (BALF). Findings 54% (7/13) bags and 46% (6/14) filters were Ultra-positive. Sequencing read counts and microbial diversity did not differ across bags, filters, and sputum. However, microbial composition in bags (Sphingobium-, Corynebacterium-, Novosphingobium-enriched) and filters (Mycobacterium-, Sphingobium-, Corynebacterium-enriched) each differed vs. sputum. Furthermore, sequencing only detected Mycobacterium in bags and filters but not sputum. In the subset, bag and filter microbial diversity did not differ vs. oral washes or BALF but microbial composition differed. Bags vs. BALF were Sphingobium-enriched and Mycobacterium-, Streptococcus-, and Anaerosinus-depleted (Anaerosinus also depleted in filters vs. BALF). Compared to BALF, none of the aerosol-enriched taxa were enriched in oral washes or sputum. Interpretation PMC captures aerosols with Ultra-detectable MTBC and MTBC is more detectable in aerosols than sputum by sequencing. The aeromicrobiome is distinct from sputum, oral washes and BALF and contains differentially-enriched lower respiratory tract microbes.